2020
DOI: 10.1177/1120672120914230
|View full text |Cite
|
Sign up to set email alerts
|

Transscleral versus endoscopic cyclophotocoagulation outcomes for refractory glaucoma

Abstract: Objectives: Evaluate the efficacy of transscleral cyclophotocoagulation versus endoscopic cyclophotocoagulation to reduce intraocular pressure. Methods: A retrospective, non-randomized cohort study with 1 year of follow-up included 62 eyes of 62 refractory glaucoma patients who underwent transscleral cyclophotocoagulation or endoscopic cyclophotocoagulation. Results: Thirty-two patients were enrolled in transscleral cyclophotocoagulation group and 30 patients in endoscopic cyclophotocoagulation group, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…A randomized clinical trial comparing ECP with alternatives has never been conducted (Tóth et al 2019). To date, only one non‐randomized study has compared ECP (30 patients) to CW‐TSCPC (32 patients) (Lanzagorta‐Aresti et al 2020). It has shown that both ECP and CW‐TSCPC effectively lowered the IOP after a one‐year follow‐up.…”
Section: Cw‐tscpc and Ecpmentioning
confidence: 99%
“…A randomized clinical trial comparing ECP with alternatives has never been conducted (Tóth et al 2019). To date, only one non‐randomized study has compared ECP (30 patients) to CW‐TSCPC (32 patients) (Lanzagorta‐Aresti et al 2020). It has shown that both ECP and CW‐TSCPC effectively lowered the IOP after a one‐year follow‐up.…”
Section: Cw‐tscpc and Ecpmentioning
confidence: 99%
“…97,110 BCVA loss ≥ 2 was between 6% and 38.8% in these 2 studies. 97,110 Like with other CPC modalities, phthisis is a rare potential complication after ECP. 111…”
Section: Complications Of Cyclophotocoagulation (Cpc)mentioning
confidence: 84%
“…In medium- to large-sized retrospective studies investigating eyes that had cataract surgery with ECP, adverse events included anterior chamber fibrin (10.6%), macular edema (4.8% to 8.7%), persistent iritis (3.6%), corneal decompensation (2.9%), IOP spike (1.2% to 7.7%), retinal detachment (1.2%), Descemet’s detachment (1.2% to 1.9%), and zonular dialysis (1.0%) 107–109 . In the study by Rodrigues et al,[107] BCVA loss ≥ 2 lines was 2.2% In medium-sized retrospective studies evaluating standalone ECP, adverse events included macular edema (4.8% to 13%), anterior chamber fibrin (2.4% to 33%), persistent iritis (4.8%), hypotony (4.8%), choroidal effusion (3%), corneal decompensation (2.4% to 9.5%), retinal detachment (2.4%), and suprachoroidal hemorrhage (2.4%) 97,110 . BCVA loss ≥2 was between 6% and 38.8% in these 2 studies 97,110 .…”
Section: Complications Of Cyclophotocoagulation (Cpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, more well‐designed RCTs and clinical data with larger sample sizes and longer follow‐ups are warranted. Future research should also look into long‐term outcomes, cost–benefit analysis, and quality‐of‐life measurements and may further investigate newer technologies, if more studies and data are available, such as micropulse transscleral laser therapy, endoscopic cyclophotocoagulation, and high‐intensity focused ultrasound cyclodestructions (Abdelrahman & El Sayed, 2018; Aquino et al, 2015; Beardsley et al, 2017; Giannaccare et al, 2017; Graber et al, 2018; Kraus et al, 2014; Lanzagorta‐Aresti et al, 2021).…”
Section: Discussionmentioning
confidence: 99%